Trends in intensive neonatal care during the COVID-19 outbreak in Japan. Issue 3 (23rd November 2020) - Maeda, Yuto; Nakamura, Masaki; Ninomiya, Hideki; Ogawa, Kohei; Sago, Haruhiko; Miyawaki, Atsushi
Abstract : The reduction in the use of neonatal intensive care units (NICUs) during the COVID-19 outbreak has been reported, but whether this phenomenon is widespread across countries is unclear. Using a large-scale inpatient database in Japan, we analysed the intensive neonatal care volume and the number of preterm births for weeks 10–17 vs weeks 2–9 (during and before the outbreak) of 2020 with adjustment for the trends during the same period of 2019. We found statistically significant reductions in the numbers of NICU admissions (adjusted incidence rate ratio (aIRR), 0.76; 95% CI, 0.65 to 0.89) and neonatal resuscitations (aIRR, 0.37; 95% CI, 0.25 to 0.55) during the COVID-19 outbreak. Along with the decrease in the intensive neonatal care volume, preterm births before 34 gestational weeks (aIRR, 0.71) and between 34 0/7 and 36 6/7 gestational weeks (aIRR, 0.85) also showed a significant reduction. Further studies about the mechanism of this phenomenon are warranted.